Distinct Alterations in ATP‐Binding Cassette Transporter Expression in Liver, Kidney, Small Intestine, and Brain in Adjuvant‐Induced Arthritic Rats. Issue 8 (9th June 2014) - Kawase, Atsushi; Norikane, Sari; Okada, Ayaka; Adachi, Mamiko; Kato, Yukio; Iwaki, Masahiro
<x xml:space="preserve">Abstract</x> Pathophysiological changes of infection or inflammation are associated with alterations in the production of numerous absorption, distribution, metabolism and excretion‐related proteins. However, little information is available on the effects of inflammation on the expression levels and activities of ATP‐binding cassette (ABC) transporters. We examined the effect of acute (on day 7) and chronic (on day 21) inflammation on the expression of ABC transporters in some major tissues in rat. Adjuvant‐induced arthritis (AA) in rats was used as an animal model for inflammation. The mRNA levels of mdr1a and mdr1b encoding P‐glycoprotein (P‐gp) decreased significantly in livers of AA rats on day 21. Hepatic protein levels of P‐gp, Mrp2, and Bcrp decreased significantly in membranes but not homogenates of AA rats after 7 days and after 21 days of treatment with adjuvant. Contrary to liver, protein levels of P‐gp and Mrp2, but not Bcrp in kidney, increased significantly in membranes. The biliary excretion of rhodamine 123 was decreased in rats with chronic inflammation owing to decreases in efflux activities of P‐gp. Our results showed that the expression of transporters in response to inflammation was organ dependent. In particular, hepatic and renal P‐gp and Mrp2 exhibited opposite changes in membrane protein levels. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2556–2564, 2014